Science and Geopolitics in the Origins of the Green Revolution - Picado, Wilson (2008)
In this article, the influence of geopolitics is analyzed in the case of spreading seeds of high-yielding varieties in the Third World, through study cases in Mexico, India and Costa Rica. In Mexico, agricultural research, supported by the Rockefeller Foundation since 1943, allowed the development of high-yielding varieties of wheat. In India, the cradle of the so-called Green revolution, the arrival of these seeds happened within the frame of the expansion of communism in Southeast Asia, and the resulting interest of the United States in controlling social conflicts. In the case of Costa Rica, its strategic position in relation to the Panama Canal, in-volved a remarkable interest of the United States in the development of a program for food production that would prepare the land so that, years later, the seeds and the Green revolution technology would be accepted.